Curcumin Prevents Free Fatty Acid-Induced Lipid Accumulation via Targeting the miR-22-3p/ CRLS1 Pathway in HepG2 Cells - Yuanyuan Mei; Xiaoting Sun; Shi-Ying Huang; Xiaowen Wu; Kuo-Ting Ho; Liming Lu; Chaoxiang Chen; Jian Li; Jingwen Liu; Guiling Li (Polish Journal of Food and Nutrition Sciences)
Dysregulated lipid metabolism in liver is an important hallmark of non-alcoholic fatty liver disease (NAFLD), which may be modulated by dietary polyphenols or microRNAs (miRNAs). However, the underlying epigenetic regulatory mechanism of polyphenols remain unclear. The current study aimed to address how miRNA mediates hepatic lipid metabolic control of curcumin, a polyphenolic food supplement. The results showed that 24 h treatment with 5 - 20 μM curcumin prevented free fatty acid-induced lipid accumulation by around 10 ~ 50% in HepG2 cells, which was attenuated by pre-transfection with 40 nM miR-22-3p mimic for 48 h. In consequence, transfection with 40 nM miR-22-3p inhibitor for 48 h significantly reduced lipid accumulation by around 10%. And 48 h overexpression of miR-22-3p targeting cardiolipin synthase 1 ( CRLS1 ) gene, which encodes a mitochondrial phospholipid synthase, showed a similar regulatory effect. Thus, miR-22-3p and CRLS1 showed opposite effects in modulating lipid metabolism, which probably involved mitochondrial control. In summary, this study demonstrated that curcumin improved hepatic lipid metabolism via targeting the miR-22-3p/ CRLS1 pathway. Identification of the epigenetic regulatory mechanism underlying lipid metabolism may thereby facilitate alleviation of metabolic disorders by natural polyphenols.